Two concepts of the rule of law - Auersperger Matić, Andrej (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2019)
The rule of law is today one of the leading notions in international relations and an object of intense public debate in many countries. As a legal and political ideal, it is invoked to argue for greater recognition of law and legal institutions in modern society. This is happening even if there is no generally accepted understanding of what it actually is in either political or legal terms, and its meaning can differ considerably depending on the social and geographical environment. To facilitate the contemporary rule of law debate, this article proposes a primary distinction between what might be termed classical and institutional interpretations of this concept. It is suggested that under the classical view, the rule of law is understood as a constitutional principle, broadly expressing liberal doctrines on the proper relationship between law, the individual and the modern constitutional state. In the last few decades, however, we have also witnessed, especially in the international context, the appearance of another, more general and empirical usage of the term, applied mainly in relation to the working of legal institutions. References to the rule of law of this kind are characterised by questions about whether and how law works in practice, not just in relation to the state but also in relations between individuals. This version of the rule of law is often strongly associated with the working of judicial institutions and dispute resolution procedures. The institutional view of the rule of law therefore helpfully supplements the classical view with new elements that highlight institutional objectives in legal and public discourse about the legitimacy of law.
Keywords: constitutional principles; effectiveness of justice; international organisations; legal theory; mednarodne organizacije; rule of law; teorija prava; učinkovitost pravosodja; ustavna načela; vladavina prava